Planning compliant motion strategies - Buckley, S.J. (Proceedings IEEE International Symposium on Intelligent Control 1988, 1988)
A planning program which synthesizes compliant motion strategies, in which an object in the grasp of a robot slides along obstacles in an attempt to reach a goal region, is described. The input to the planner is a model of the task geometry, a start region, and a goal region. To make the planning problem tractable, the task geometry is reduced to a finite state space, whose states are collections of vertices, edges, and faces from the configuration space of the robot. Strategy synthesis is complicated by uncertainty in the starting configuration of the robot and in robot sensing and control. The planner synthesizes compliant motions which are guaranteed to perform state transitions despite uncertainty. Using best first search, compliant motions are synthesized until a strategy is found from the start state to a goal state. A double-hole environment for which the planner produced a compliant motion strategy is shown. The planner was also tested successfully on two other configuration space environments, a cube and a single hole. The single-hole strategy was successfully executed on an IBM 7565 robot. The implemented program represents the first general-purpose compliant motion planner to generate multistep strategies.< >